Penguatan Literasi Statistik Bagi Tenaga Administrasi dalam Pengelolaan Data Santri di Pondok Pesantren AL-Madinatul Islamiyah Rumeneng Desa Paok Motong Kecamatan Masbagik - Ratna Yuniarti; Hartiani Hartiani; Harizahayu Harizahayu (Lembaga Pengembangan Kinerja Dosen, 2025)
The role of administrative staff in Islamic boarding schools is very central in ensuring the smooth functioning of the institution. One of the important competencies that need to be possessed is statistical literacy, which includes the ability to understand, process, and present data systematically. The purpose of this PKM activity is to improve the knowledge and skills of administrators in applying statistics to administrative management. With an understanding of concepts, insight into the application of statistical concepts, accuracy of interpretation of statistical results, and visualization and communication skills of statistical analysis results. This community service activity is carried out through workshops and intensive mentoring. The results of this activity indicate that efforts to improve the knowledge and skills of partners in managing student administration through strengthening statistical literacy have gone well and provided quite optimal results, especially in the indicators of skills in calculating and visualizing data.